Assessment of a Light Unmanned Aircraft Ground Impact Energy - Skobir, Zmago; Magister, Tone (Promet - Traffic&Transportation, 2012)
The subject of investigation are unmanned aircraft lighter than 150kg under control by national aviation authorities and therefore prudently requiring harmonized individual state regulations. Originated from a general premise that the unmanned aircraft regulations should evolve from the existing standards for manned aircraft of equivalent class or category, the light fixed wing unmanned aircraft equivalence to the manned aircraft is defined in the form of sets of equivalency and non-equivalency based on the established administrative type of methodology of impact kinetic energy comparison. The basic flight characteristics of the existing operational light fixed wing unmanned aircraft are analyzed assuring proper input for determination of the more realistic unmanned aircraft impact kinetic energy in controlled and uncontrolled flight into terrain crash scenarios used for the evaluation of established methodology adequacy for equivalence determination. It is shown in the paper that determination of the unmanned aircraft equivalency to the manned aircraft should not be based on the unmanned aircraft maximum take-off mass nor their airspeed range alone.KEYWORDS: light unmanned aircraft, impact kinetic energy, hazard potential, classification